A new species of Pristimantis (Amphibia, Anura, Strabomantidae) from a montane forest of the Pui Pui Protected Forest in central Peru - Edgar Lehr; Jiří Moravec; Yingtong Wang; Marek Uvizl (ZooKeys)
Herpetological inventories conducted in the Pui Pui Protected Forest in the central Peruvian Andes between 2012 and 2014 revealed unusually high local anuran richness and endemism. Herein, we describe a new species of Pristimantis discovered in the buffer zone of the protected area between 1550 and 1730 m a.s.l. The description is based on one subadult male (snout–vent length 14.4 mm), one adult female (snout–vent length 26.4 mm), and six juvenile specimens collected in the montane forest between 1550 and 1730 m a.s.l. DNA barcoding placed P. vrazi sp. nov. as the sister taxon to P. rhabdocnemus and in the clade also containing P. lindae, P. sinschi, P. quaquaversus, and one still unnamed Pristimantis species. Pristimantis vrazi sp. nov. differs from all these closely related species by the combination of the following characters: tuberculate dorsum, presence of the tympanum, presence of dentigerous processes on the vomer, absence of vocal slits, a red median horizontal streak across the iris, a narrow black median vertical streak on the lower half of the eye, cream to dark brown dorsal ground coloration, and cream to gray ventral ground coloration.